2017
DOI: 10.1111/coa.12990
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous opioid drug abuse as an independent risk factor for supraglottic squamous cell carcinoma—A case‐control study

Abstract: Intravenous opioid drug abuse represents an independent risk factor for SG-SCC. The pathogenesis should be investigated not just as a risk factor, as opioids are commonly used for pain management in oncologic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Our findings of an increased risk of HNSCC are in agreement with those of five prior case‐control studies 6,8‐11 . The only study that differed was a cross‐sectional study of 44 laryngeal cancers.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings of an increased risk of HNSCC are in agreement with those of five prior case‐control studies 6,8‐11 . The only study that differed was a cross‐sectional study of 44 laryngeal cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of an increased risk of HNSCC are in agreement with those of five prior case-control studies. 6,[8][9][10][11] The only study that differed was a cross-sectional study of 44 laryngeal cancers. It showed no association of opium dependency and the pattern of laryngeal anatomic regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study conducted in Tehran, Iran, also showed that after controlling the effect of smoking, O and D use increased the risk of laryngeal cancer about 6 times (95% CI:1.10-33.23) (Bakhshaee et al, 2017). In a recent study, in Israel a significant relation was observed between IV (intravenous) O and D use and Supraglottic Squamous Cell Carcinoma and the odds ratio for patients with an IVDA history to have SG-SCC relative to G-SCC was 10.84 (95% CI: 1.3-89.4) (Shoffel-Havakuk et al, 2017). Another study showed the odd ratio between opium use and the risk of oral cancers (tongue, palate, and buccal), to be 4.0 (95% CI: 1.2-13.6) (Razmpa et al, 2014).…”
Section: Discussionmentioning
confidence: 96%